Documentos sobre oficinas de correo "Postmaster" de San Juan - Todd, Roberto H.; Veve, Julio; Bartlett, John H. (My University, 1922)
Documentos sobre oficinas de correo "Postmaster" de San Juan.
Keywords: Postal service--Puerto Rico.; Servicio postal--Puerto Rico.; Meléndez, Eleuterio Jr.; Gay, John; Siegmund, Chester W.; Montgomery Reily, Emmet, 1866-1954; Montilla, Fernando